Monitoring the Future: A Continuing Study of American Youth (12th-Grade Survey), 1995 - Johnston, Lloyd D. ([Verlag nicht ermittelbar], 1997)
This is the 21st annual survey in this series that explores changes in important values, behaviors, and lifestyle orientations of contemporary American youth. Two general types of tasks may be distinguished. The first is to provide a systematic and accurate description of the youth population of interest in a given year, and to quantify the direction and rate of change occurring over time. The second task, more analytic than descriptive, involves the explanation of the relationships and trends observed. Each year, a large, nationally representative sample of high school seniors in the United States is asked to respond to approximately 100 drug-use and demographic questions as well as to an average of 200 additional questions on a variety of subjects, including attitudes toward government, social institutions, race relations, changing roles for women, educational aspirations, occupational aims, and marital and family plans. The students are randomly assigned one of six questionnaires, each with a different subset of topical questions but all containing a set of "core" questions on demographics and drug use. There are about 1,400 variables across the questionnaires.